Analysis of solid tumor mutation profiles in liquid biopsy. (27th September 2018) - Balaji, Sai A.; Shanmugam, Ashwini; Chougule, Anuradha; Sridharan, Srikant; Prabhash, Kumar; Arya, Anuradha; Chaubey, Aditya; Hariharan, Arun; Kolekar, Pandurang; Sen, Manimala; Ravichandran, Aarthi; Katragadda, Shanmukh; et al.
Abstract: Liquid biopsy is increasingly gaining traction as an alternative to invasive solid tumor biopsies for prognosis, treatment decisions, and disease monitoring. Matched tumor‐plasma samples were collected from 180 patients across different cancers with >90% of the samples below Stage IIIB. Tumors were profiled using next‐generation sequencing (NGS) or quantitative PCR (qPCR), and the mutation status was queried in the matched plasma using digital platforms such as droplet digital PCR (ddCPR) or NGS for concordance. Tumor‐plasma concordance of 82% and 32% was observed in advanced (Stage IIB and above) and early (Stage I to Stage IIA) stage samples, respectively. Interestingly, the overall survival outcomes correlated to presurgical/at‐biopsy ctDNA levels. Baseline ctDNA stratified patients into three categories: (a) high ctDNA correlated with poor survival outcome, (b) undetectable ctDNA with good outcome, and (c) low ctDNA whose outcome was ambiguous. ctDNA could be a powerful tool for therapy decisions and patient management in a large number of cancers across a variety of stages. Abstract : This study examines the tumor‐plasma concordance in seven cancer types across stages. A concordance of 82% and 32% was observed in advanced (Stage IIB and above) and early (Stage I to Stage IIA) stage samples, respectively. Overall survival outcomes correlated well to presurgical/at‐biopsy ctDNA levels.